Financial Literacy Level and Money Management : A Study From Financial Student of Management Study Program at State University of Makasar - Aslam, Annisa Paramaswary (International Humanity Advance, Business & Sciences, 2024)
This study aims to know about the level of financial literacy of 100 students concentrating on financial management at the Management Study Program at Makassar State University. Data primary is used to this research with 100 sample. This study used a regression multiple. The results of research found that credit literation, saving literation, and investment literation affect the management and decision-making of student finances, the higher the student's financial literacy, the better the management and decision-making. But, the spending literation doesn’t significant effect on financial management